Ornamen Naga Dalam Konteks Kain Batik, Estetika, Budaya Jawa dan Tionghoa Di Indonesia - Rahmanu Widayat (Mudra Jurnal Seni Budaya, 2022)
This paper was created to discuss an interesting issue, dragon ornament in batik cloth, the value of its aesthetics, and its context to Javanese and Tionghoa (Chinese) culture in Indonesia. This paper attempts to answer several questions including what is a dragon ornament, why is a dragon ornament applied to batik cloth, how is it aesthetic, and how is the relationship between Javanese and Tionghoa dragon ornaments in Indonesia. This issue is approached using interpretation perspective, both specifically in the context of batik cloth and its aesthetics, as well as in a broader context of Javanese and Tionghoa cultures. The interesting findings show that dragon ornaments on classical batik cloth in the form of Javanese dragons and Chinese dragons have their respective characteristics. Dragon ornament is applied to batik cloth due to its visual beauty and meaning as a protector and symbol of power that is identical to the king or emperor. The two Javanese and Chinese dragon ornaments not only adorn batik cloth, but are also applied for the benefit of architecture and other art works. Specific findings indicate that Chinese dragon ornaments are more developed than Javanese dragon ornaments, especially for contemporary batik fashion. Another finding is that the Parang motif combined with the Chinese dragon looks aèng or strange but is favoured by the public. This article suggests that batik producers develop Javanese dragon motifs for contemporary batik (preservation with new functions). For researchers, in studying dragon ornaments, the use of Western and Eastern aesthetic approaches will complement each other and result in more comprehensive findings. Another phenomenon that is intriguing for future research is the presence of batik producers and online shops that offer batik products with a variety of motifs and patterns. It is an interesting phenomenon to be studied in terms of design and marketing.